Interrogating the whole-genome shotgun sequence of Escherichia coli sequence type 127 strain 1538RHQ, which harbors virulent antigenic factors, isolated from a mastitic cow - Ali, Bashir; Zakaria, Zunita; Abdullah, Faez Firdaus Jesse; Ramanoon, Siti Zubaidah; Mohd Lila, Mohd Azmi (American Society for Microbiology, 2019)
We report the whole-genome sequence of Escherichia coli sequence type 127 (ST127) strain 1538RHQ, recovered from a mastitic cow in a dairy herd in Selangor, Malaysia. The objective of this study was to identify the antigenic and virulence properties that can be used as suitable targets for vaccine development against bovine mastitis.